(untitled) (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
In coercive cases, Chinese nominal classifiers function as syntactic triggers that initiate the entire process of recategorization and reinterpretation of nouns, while simultaneously providing relevant cues for the construction of context. Within the framework of the operational model of the Universals and Typology Project (UNITYP), this article analyzes the roles performed by Chinese nominal classifiers in coercion, such as the apprehension of objects, the construction of syntactic relations, nominal reclassification, pluralization, anaphoric identification, and the mutual conversion between proper names and common nouns. A small investigation is conducted on the basis of a parallel corpus with the purpose of examining how Spanish resolves the coercion imposed by nominal classifiers. The study concludes that Spanish, lacking nominal classifiers, resorts to diverse morphological and lexical instruments to resolve this type of coercion. This research not only contributes to a deeper understanding of the syntactic and semantic functions of Chinese nominal classifiers but also offers practical implications for Chinese language teaching and translation between the two languages, facilitating more effective strategies to manage structural differences.